Factors Influencing Career Choice among Business Administration Students of Pokhara University (The Batuk, 2022)
Career development theories imply that various factors might influence students' career choices. The study examined the existent factors influencing career choice among business administration students of Pokhara University. A quantitative paradigm guided the study. A purposive sample of 303 undergraduate and postgraduate students participated in the study. The data was collected using the Career Choice Scale (CCS), which looked at the four components of career choice: intrinsic, extrinsic, interpersonal, and institutional influences. The analysis of data was performed with SPSS and Amos. The results demonstrated that four factors, intrinsic factors such as personal interest, advancement in career, and personality traits; extrinsic factors such as prestigious job, well-paying employment, and job security; interpersonal factors such as parental support and influence, the influence of older siblings and peer influence, and institutional factors such as career counseling activities, teachers and educators’ impact; type of academic program offered were found influential factors. The findings may have implications for Nepalese higher education institutions to guide and counsel students interested in a career in management. Understanding how students make career decisions allows efforts to guide students toward more realistic career choices.